Analisis Kinerja Keuangan Dengan Menggunakan Metode MVA (Market Value Added) Pada PT. Bank Panin Dubai Syariah - Nur Ayu Istiqomah; Karnila Ali; Febriyanto (Jurnal Manajemen DIVERSIFIKASI, 2025)
The development of today's This study aims to determine the financial performance of PT.Bank Panin Dubai Syariah using the Market Value Added (MVA) method. Based on theresults of Market Value Added (MVA) analysis at PT. Bank Panin Dubai Syariah for the last3 years, namely 2019-2021, has shown a pretty good increase, this proves that the companyis able to manage capital so that the profits generated increase. But in 2020 the companyexperienced a very significant decline. Then with the analysis of Market Value Added (MVA)at PT. Bank Panin Dubai Syariah in 2019-2020 has a good value which shows added valuefor the Company